2017
DOI: 10.18632/oncotarget.20251
|View full text |Cite
|
Sign up to set email alerts
|

Hormone receptors expression in ovarian cancer taking into account menopausal status: a retrospective study in Chinese population

Abstract: Ovarian cancer is a major gynaecological cancer with different subtypes and studies have suggested that estrogen receptor (ER) or progesterone receptor (PR) positivity are associated with better clinical outcomes. Furthermore, the clinical outcomes of ovarian cancer are better in Asian compared to Caucasian. To date, studies investigating the ER or PR positivity in all subtypes of ovarian cancer, including borderline epithelial, are limited. In this retrospective study we investigated ER and PR positivity in C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 33 publications
2
9
0
Order By: Relevance
“…It has been suggested that these histotypes may respond to hormonal therapy [38][39][40]. The percentage of ER+ cases we observed (10.6%) is consistent with a recent OTTA study, which found that 16% of MOC had strong ER expression [37], but others report rates as low as 4% up to 19% [41][42][43][44]. None of the MOC cases in our cohort appear to have received hormonal therapy, hence hormonal response data within this cohort is unknown.…”
Section: Discussionsupporting
confidence: 88%
“…It has been suggested that these histotypes may respond to hormonal therapy [38][39][40]. The percentage of ER+ cases we observed (10.6%) is consistent with a recent OTTA study, which found that 16% of MOC had strong ER expression [37], but others report rates as low as 4% up to 19% [41][42][43][44]. None of the MOC cases in our cohort appear to have received hormonal therapy, hence hormonal response data within this cohort is unknown.…”
Section: Discussionsupporting
confidence: 88%
“…The expression of estrogen receptor (ER) and progesterone receptor (PR) in ovarian tissue (n = 894) was measured by immunohistochemistry on paraffin-embedded sections and read automatically (Leica Bond III, Germany) as described previously 40 . In the current study, 577 cases overlapped with previous study 40 . Briefly, antigen retrieval was performed by heating in Bond epitope retrieval solution 2 (ph 9.0) for 20 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…Likewise, the risk of epithelial ovarian cancer is increased by long-term exposure to estrogen, as occurs in early menarche, late menopause, and in the context of hormone replacement therapy [ 13 , 14 ]. Indeed, one study of 394 serous epithelial ovarian cancer patients reported that 86% of tumors were ER-positive [ 15 ]. Moreover, when ER-positive epithelial ovarian cancer cells were implanted in the peritoneal cavity of mice, estrogen significantly increased tumorigenesis, promoted lymph node metastasis, and decreased survival [ 16 , 17 ].…”
Section: Hormone-dependent Cancersmentioning
confidence: 99%
“…Accounting for almost 90% of cases, epithelial ovarian cancers are classified into several subtypes, of which serous tumors are the most notable [ 66 ]. A key study reported that 86% of serous epithelial ovarian tumors are ER-positive [ 15 ]. In vitro, estrogen can stimulate the proliferation of ER-positive ovarian cancer cell lines [ 69 ].…”
Section: Role Of Greb1 In Ovarian Cancermentioning
confidence: 99%